Inflammatory profile of chronic apical periodontitis: a literature review. (3rd April 2019) - Braz-Silva, Paulo Henrique; Bergamini, Mariana Lobo; Mardegan, Andressa Pinto; De Rosa, Catharina Simioni; Hasseus, Bengt; Jonasson, Peter
Abstract: Apical periodontitis caused by root canal infection is the most frequent pathological lesion in the jaws, mainly manifested as periapical granulomas and cysts. Understanding of the formation and progression of apical periodontitis as well as the identification of inflammatory biomarkers can help increase the knowledge of pathogenic mechanisms, improve the diagnosis and provide support for different therapeutic strategies. The objective of the present article is to review inflammatory biomarkers such as cytokines, chemokines, inflammatory cells, neuropeptides, RANK/RANKL/OPG system and other inflammatory markers and to relate these systems to the development and progression of pathological conditions related to apical periodontitis.